FORMULATION OF VITAMIN C GEL SERUM USING SODIUM ALGINATE FROM BROWN ALGAE (Sargassum polycystum) AS GELLING AGENT (Universitas Negeri Semarang, 2022)
Background : Brown algae contains alginate which can be used as a gelling agent on cosmetics product. In this study, alginates from brown algae can be formulated on antioxidant serum gel. Vitamin C was used as a model of active ingredient which are known as potent antioxidants. In order to obtain a serum gel preparation with good physical characteristics, optimization was also carried out in the formula between sodium alginate as a gelling agent and propylene glycol as a humectant. Aim : The purpose of the research is to determine the yield of sodium alginate produced from brown algae extraction, and determine the optimum ratio between sodium alginate and propylenglycol to provide good physical characteristics for vitamin C serum gel. Method : The extraction method used to obtain sodium alginate from brown algae Sargassum polycystum using the acid pathway extraction method. The method used to optimize sodium alginate and propylenglycol is the Simplex Latice Design method with Design Expert software version 10.0.1. Optimization parameters included tests of viscosity, spreadability, adhesion, and pH. Penetration test using franz diffusion cells, and the stability test of the preparation using the cycling test method. Result : The yield of sodium alginate extraction was 20.61%. Results of analysis software Design Expert version 10.0.1 show that sodium alginate could increase the response of viscosity, adhesion, and pH, also reduce the spreadability of vitamin C serum gel. While, propylenglycol could increase all the responses. Conclusion : The yield of brown algae (Sargassum polycystum) obtained was 20.61% with the combined composition with propylene glycol in the preparation of serum gel vitamin C being 7.56% : 10.44%.